Performance Analysis of Islamic Equity Mutual Funds and Conventional Equity Mutual Funds During 2019-2023 Period - Naila Yumna Shafwah; Wiku Suryomurti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze and compare the performance of Islamic equity mutual funds and conventional equity mutual funds in Indonesia during the 2019–2023 period, particularly throughout the pandemic and post-pandemic phases. The method employed is descriptive quantitative with a comparative approach involving 18 Islamic and 56 conventional mutual funds registered in Bareksa. Performance is assessed using three risk-adjusted return metrics: Sharpe Ratio, Treynor Ratio, and Jensen’s Alpha, based on monthly NAV data and benchmarked against JCI and ISSI. The findings reveal that, on average, both fund types showed negative performance under Sharpe and Treynor, while Islamic funds outperformed in Jensen’s Alpha, indicating superior excess returns beyond systematic risk expectations. T-test results indicate no significant differences between the two fund types across all three performance indicators. These findings imply that Islamic equity mutual funds can be a viable investment alternative, especially for investors seeking Sharia-compliant options.